INTERAKSI SENI PERTUNJUKAN WAYANG DAN POLITIK - Jaka Rianto (Gelar : Jurnal Seni Budaya, 2009)
The article entitled â€œWayang and Politics: the Interaction of Shadow Play with the Power Systemâ€ discusses the intervention of the authority in puppet theatre. The intervention has begun since there was an understanding that art could be a medium for practical purposes. Based on the fact, this article aims to explain the problems of how the power system intervenes wayang theatre and what the wayang paradigm in the Indonesian power system is like. Based on the analysis on political system dimension, the result of the research showed that to make the art development free from the intervention of the authority was hard to realize. Wayang theatre, indeed, can be used as the frame of the behaviour of the authority. We can see, for instance, that politicians are analogous to wayang; there is a belief that wayang ruwatan (an act of exorcism) performance aims at making a certain political party win.Keyword : wayang performance, politics, power